Empathy (IntechOpen, 2023)
Empathy - Advanced Research and Applications is a compilation of recent experimental studies and theoretical models on the concept of empathy and its implication in various aspects of social life. The book describes the multifaceted construct of empathy and presents arduous concepts in a fluent and understandable way to reach readers who may not be familiar with the subject. Through this book, readers will understand the importance of empathetic skills and the neurological and psychological mechanisms of empathy. There is even the possibility to learn and improve one’s empathetic ability. Empathy is vital for society’s wellness and we hope that this book serves as a springboard for future research in the field.